Sie sind auf Seite 1von 4

9.

Circles
Solutions
Section A −4 − 2
(b) Slope of PC =
2−4
4 × 3 − 3 × (−2) + 2 =3
1. (a) d=
4 2 + (−3) 2 Slope of AB = (−1) ÷ 3
1
20 =−
= 3
5
Equation of AB is
=4 1
y − 2 = − ( x − 4)
3
(b) Radius of circle = 4 3y − 6 = −x + 4
∴ Equation of circle is x + 3 y − 10 = 0
( x − 3) 2 + [ y − (−2)] 2 = 4 2
x 2 − 6 x + 9 + y 2 + 4 y + 4 = 16 3. (a) Let the family of circles be
x 2 + y 2 − 6x + 4 y − 3 = 0 F : x 2 + y 2 + 2x − 5
+ k ( x 2 + y 2 + 4 x − 6 y + 12) = 0
 − (−4) −8  (1 + k ) x 2 + (1 + k ) y 2 + (2 + 4k ) x − 6ky
2. (a) Centre =  , 
 2 2  + (−5 + 12k ) = 0
= (2, − 4) If 1, 2) lies on F, then
(−
Distance between centre and (4, 2) (1 + k ) × (−1) 2 + (1 + k ) × 2 2 + (2 + 4k )(−1)
= (2 − 4) 2 + (−4 − 2) 2 − 6k × 2 + (−5 + 12k ) = 0
1 + k + 4 + 4k − 2 − 4k − 12k − 5 + 12k = 0
= 4 + 36
k −2 = 0
= 40
k =2
Radius = 2 2 + (−4) 2 − (−36) ∴ The equation of C is
= 4 + 16 + 36 (1 + 2) x 2 + (1 + 2) y 2 + (2 + 4 × 2) x
= 56 − 6 × 2 y + (−5 + 12 × 2) = 0
AP = PB 3 x 2 + 3 y 2 + 10 x − 12 y + 19 = 0
∴ PC ⊥ AB
In ∆APC , (b) Equation of C can be expressed as
AC 2 = PC 2 + AP 2 10 19
x2 + y2 + x − 4y + =0.
( 56 ) 2 = ( 40 ) 2 + AP 2 3 3
2 cm × 2 cm
AP 2 = 56 − 40  −10 − (−4) 
Centre =  , 
= 16  3× 2 2 
∴ AP = 4  5 
=  − , 2
∴ Length of chord = 4 × 2  3 
=8

1
 5
2
19 Section B
Radius = −  + 22 −
 3  3
2

5. (a) Radius =   − 2
4 D
=
9 2
2 D2 − 8
= =
3 4
2
 D2 −8 
4. (a) Substituting (−1, 2) into L, we have π×  = 2π
 4 
 
2 = −m + c
D2 −8
c = m+2 =2
4
D 2 = 16
 y = mx + c.................................(1) D = 4 or − 4 (rejected)
(b)  2
 x + y − 2 x + 4 y + 3 = 0..........(2)
2

Substituting (1) into (2),  − (−4) 0 


x 2 + (mx + c) 2 − 2 x + 4(mx + c) + 3 = 0 (b) Centre =  , 
 2 2
x 2 + m 2 x 2 + 2mcx + c 2 − 2 x = (2, 0)
+ 4mx + 4c + 3 = 0
(1 + m 2 ) x 2 + (2mc − 2 + 4m) x + c 2 + 4c + 3 = 0 42 − 8
Radius =
4
Since c = m + 2, the equation becomes
(1 + m 2 ) x 2 + [2m(m + 2) − 2 + 4m]x = 2
+ (m + 2) + 4(m + 2) + 3 = 0
2

(1 + m 2 ) x 2 + (2m 2 + 8m − 2) x (c) L1 is tangent to C.


+ m + 4m + 4 + 4 m + 8 + 3 = 0
2 ∴ Distance from (2, 0) to L1 is 2.
(1 + m ) x + 2(m + 4m − 1) x
2 2 2
2−0+c
= 2
+ (m + 8m + 15) = 0...................(*)
2
12 + 12
Since L touches C, the descriminant of (*) 2+c
= 2
equals to 0. 2
[2(m 2 + 4m + 1)] 2 (2 + c) 2 = 4
− 4(1 + m )(m + 8m + 15) = 0
2 2
2 + c = 2 or − 2
(m 4 + 16m 2 + 1 + 8m 3 − 8m − 2m 2 ) c = 0 or − 4 (rejected)
− (m 2 + 8m + 15 + m 4 + 8m 3 + 15m 2 ) = 0 ∴ Equation of L1 is y = x.
− 2m 2 − 16m − 14 = 0
m 2 + 8m + 7 = 0
(m + 1)(m + 7) = 0
m = −1 or −7 (rejected)
c = m+2
= 1

2
L2 is tangent to C. 4
7 − (− )
∴ Distance from (2, 0) to L2 is 2. tan θ 1 = 3
4
2+0−d 1 + (− )(7)
= 2 3
12 + 12 = −1
2−d θ 1 = 45°
= 2
2 0 − (−6)
(2 − d ) 2 = 4 (ii) Slope of BD =
6 − (−2)
2 − d = 2 or − 2 3
=
d = 4 or 0 (rejected) 4
∴ Equation of L2 is x + y = 4. 0 − (−7)
Slope of CD =
 y = x.......................(1) 6−5
 =7
 x + y = 4................(2)
3
Substituting (1) into (2), we have −7
x+x=4 tan θ 2 = 4
3
2x = 4 1+ × 7
4
x=2 = −1
∴ y=2
θ 2 = 45°
The coordinates of P = (2, 2)

(b) Since ∠BAC = ∠BDC ,


(d) Distance between centre and P = 2 − 0
∴ A, B, C and D are concyclic.
=2
(converse of ∠s in same segment)
∠CBP = 90° (tangent perp. to radius)
∴ ABCD is a cyclic quadrilateral.
PB 2 + CB 2 = PC 2 (Pythagoras’ Theorem)
PB 2 + ( 2 ) 2 = 2 2 − 7 − ( − 6)
PB 2 = 4 − 2 (c) Slope of BC =
5 − (−2)
=2 1
=−
∴ PB = 2 7
1
Slope of BC × Slope of CD = − × 7
−6 − 1 7
6. (a) (i) Slope of BA = = −1
− 2 − (−1)
∴ ∠BCD = 90°
=7
−7 − 1 ∴ BD is a diameter of the circle.
Slope of CA = (converse of ∠ in semicircle)
5 − (−1)
4  −2 + 6 −6 + 0 
=− Centre =  , 
3  2 2 
= (2, −3)
1
Radius = (−2 − 6) 2 + (−6 − 0) 2
2
1
= 64 + 36
2
=5

3
Equation of circle is
( x − 2) 2 + ( y + 3) 2 = 5 2
( x − 2) 2 + ( y + 3) 2 = 25

(d) Slope of the line joining centre and A


−3 − 1 4
= =−
2 − (−1) 3
 4
Slope of tangent at A = (−1) ÷  − 
 3
3
=
4
Equation of tangent at A is
3
y − 1 = [ x − (−1)]
4
4 y − 4 = 3x + 3
3x − 4 y + 7 = 0................(1)
Slope of the line joining centre and D
−3 − 0 3
= =
2−6 4
3
Slope of tangent at D = (−1) ÷
4
4
=−
3
Equation of tangent at D is
4
y − 0 = − ( x − 6)
3
3 y = −4 x + 24
4 x + 3 y − 24 = 0.................(2)
(1) × 3 + (2) × 4 :
9 x − 12 y + 21 + 16 x + 12 y − 96 = 0
25 x − 75 = 0
x=3
Substituting x = 3 into (1),
3× 3 − 4y + 7 = 0
4 y = 16
y=4
∴ The coordinates of P = (3, 4)